Learning-Centered Leadership Practices for Effective High Schools Serving At-Risk Students. Issue 9 (September 2018) - Huff, Jason; Preston, Courtney; Goldring, Ellen; Guthrie, J. Edward
Background/Context: Modest gains in NAEP scores by American high schools over the past twenty years highlight the need to identify different factors associated with gains in student achievement. Amongst those potential factors is school leadership; limited research on leaders' work in secondary schools highlights the need to understand how high school leaders structure their schools to promote student learning. Purpose/Objective/Research Question: We ask the question, What distinguishes leaders' practices in more effective high schools from those in less effective high schools that serve large proportions of at-risk youth? Research Design: We first identify more and less effective high schools using value-added scores, and we analyze interview, observational, and survey data collected in these schools to compare and contrast how leaders support key practices and organizational routines by their staff. Our analyses include work by traditional leaders (principals and assistant principals) as well as other leaders' (e.g. department chairs, teacher leaders) practices within the schools. Conclusions/Recommendations: We found differences between higher and lower value-added schools in terms of leaders' conceptions of the intended routines (those ideal policies that faculty are to carry out) and their attention to the implementation of them, through closer examination of faculty members' actual actions or their directed support for faculty members' practices. Two primary themes characterize the differences in their practices. First, leaders in higher value-added high schools are more involved in, intentional about, and attentive to how their ideal/intended routines are implemented, thus ensuring that teachers' actual practices are changed. They focus on how these routines provide ongoing monitoring and feedback for their faculty to build and improve teachers' quality instruction, alignment of curriculum, and systems of support for students. Second, higher value-added school leaders provided more targeted, systemic efforts to support personalized learning for students.